Study of spatial variability of quality indicators during mining quartz-feldspar raw materials in the conditions of the «Girne» deposit - S.A.; А.О.; V.G.; Ye.Ye.; O.A. (Технічна інженерія, 2023)
The work is devoted to geometrization of quartz feldspar raw material deposits using modern methods and technologies. As a result of the conducted research based on the use of modern GIS and information and computer technologies, conditioned areas and areas with an increased content of harmful elements and minerals were established. Methods of geometrization of deposits of quartz feldspar raw materials were improved. On the basis of theoretical and experimental studies, the possibility of obtaining multifaceted comprehensive plans for the quantitative expression of the main indicators of the deposit has been proven, and through the mining and geometric analysis of these main characteristics with the use of modern computer and information technologies and GIS, appropriate models have been created. The obtained results can be used to divide the quarry field into technological zones depending on the content of the main indicators, and to provide recommendations on selective working out, which will allow optimizing mining operations and reducing mineral losses.